C-Terminal Fibroblast Growth Factor 23, Iron Deficiency, and Mortality in Renal Transplant Recipients - Eisenga, Michele F; van Londen, Marco; Leaf, David E; Nolte, Ilja M; Navis, Gerjan; Bakker, Stephan J L; de Borst, Martin H; Gaillard, Carlo A J M (Journal of the American Society of Nephrology, 2017)
Iron deficiency (ID) is independently associated with an increased risk of death in renal transplant recipients (RTRs). ID promotes production and cleavage of intact fibroblast growth factor 23 (iFGF23) into C-terminal fibroblast growth factor 23 (cFGF23), elevated levels of which are also prospectively associated with adverse outcomes. We hypothesized that in RTRs, the relationship between ID and mortality is mediated by FGF23. We measured plasma iFGF23 and cFGF23 levels in 700 stable RTRs at a median of 5.4 years after transplant. RTRs with ID had median (interquartile range) cFGF23 concentrations higher than those of RTRs without ID (223 [131-361] versus 124 [88-180] RU/ml; <0.001), whereas iFGF23 concentrations were similar between groups. In multivariable-adjusted Cox regression analyses, ID associated with increased mortality (81 events; hazard ratio, 1.95; 95% confidence interval, 1.22 to 3.10; <0.01). However, this association lost significance after additional adjustment for cFGF23 levels (hazard ratio, 1.45; 95% confidence interval, 0.87 to 2.51; =0.15). In further mediation analysis, cFGF23 explained 46% of the association between ID and mortality, whereas iFGF23 did not mediate this association. In conclusion, we found that cFGF23 levels are increased in iron-deficient RTRs and that the underlying biologic process driving production and cleavage of iFGF23, or alternatively the increased level of cFGF23 fragments, probably is an important mediator of the association between ID and mortality. Our results underline the strong relationship between iron and FGF23 physiology, and provide a potential mechanism explaining the relationship between ID and adverse outcome in RTRs.